Digital Participation in Democracy: The role of Social Media in the 2024 Political Campaign - Asrijal, Andi; Larisu, Zulfiah (Socious Journal, 2025)
The development of digital technology has changed the landscape of political participation, with social media becoming a major platform for political campaigns and discussions. Social media allows wider access to political information and increases public engagement in elections, especially among young voters. However, challenges such as algorithmic bias, disinformation, and political polarization increasingly threaten the integrity of democracy. The echo chamber and filter bubble phenomena cause users to only be exposed to information that is in line with their views, narrowing the space for healthy discussion. This study uses a qualitative approach with a case study method to analyze the role of social media in the 2024 Election campaign. Data were collected through interviews with political communication experts, focus group discussions (FGDs) with young voters, and analysis of campaign content on various digital platforms. The results of the study show that although social media contributes to increasing political participation, the risk of information manipulation and exploitation of user data remains a major concern. Therefore, collective efforts are needed to improve digital literacy, tighten regulations on the spread of hoaxes, and encourage transparency of social media platform algorithms. With these steps, social media can function as a more effective means of strengthening democracy and ensuring more transparent elections based on valid information.